10.0k views
0 votes
Solve -2 x + 6 = -20.

User Lastland
by
4.8k points

2 Answers

5 votes

Answer:

x = 13

Explanation:

Subtract 6 from both sides: -2x = -26

divide both side by -2 to isolate x: x = 13

User Brian Liang
by
4.5k points
7 votes

Answer:

x = 13

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define equation

-2x + 6 = -20

Step 2: Solve for x

  1. Subtract 6 on both sides: -2x = -26
  2. Divide -2 on both sides: x = 13

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: -2(13) + 6 = -20
  2. Multiply: -26 + 6 = -20
  3. Add: -20 = -20

Here we see that -20 does indeed equal -20.

∴ x = 13 is the solution to the equation.

User Hildensia
by
5.8k points